2022
DOI: 10.1001/jamasurg.2022.3338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Etomidate vs Propofol for Total Intravenous Anesthesia on Major Postoperative Complications in Older Patients

Abstract: This randomized clinical trial compares the in-hospital morbidity, clinical outcomes, and mortality associated with use of etomidate vs propofol during abdominal surgery in older patients in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…[ 19 ] In a prospective study, Woodfield et al [ 20 ] found that approximately one-third of complications occur between hospital discharge and 30 days postoperatively. Since only in-hospital POCs were considered, as reported in other studies, [ 21 , 22 ] our results might have underestimated the incidence of POCs. In addition to the hemodynamic variability observed in the PACU, our risk factors for POCs after meningioma surgery were largely congruent with those previously reported in the literature: preoperative comorbidities, higher WHO classification, longer operation time, and more intraoperative fluid administration.…”
Section: Discussionmentioning
confidence: 87%
“…[ 19 ] In a prospective study, Woodfield et al [ 20 ] found that approximately one-third of complications occur between hospital discharge and 30 days postoperatively. Since only in-hospital POCs were considered, as reported in other studies, [ 21 , 22 ] our results might have underestimated the incidence of POCs. In addition to the hemodynamic variability observed in the PACU, our risk factors for POCs after meningioma surgery were largely congruent with those previously reported in the literature: preoperative comorbidities, higher WHO classification, longer operation time, and more intraoperative fluid administration.…”
Section: Discussionmentioning
confidence: 87%
“…To the Editor Lu et al reported that, compared with propofol, etomidate anesthesia did not increase overall major in-hospital morbidity after abdominal surgery in older patients, although it induced transient adrenocortical suppression . Although etomidate-induced adrenal insufficiency is temporary, the additional effect of etomidate on adrenal function might exaggerate the adverse outcomes in the setting of baseline adrenal insufficiency .…”
mentioning
confidence: 99%
“…To the Editor I read with interest the article by Lu et al, who found that etomidate anesthesia does not increase postoperative morbidity in older patients compared with propofol. Because their findings are important to current practice, several questions deserve attention.…”
mentioning
confidence: 99%